Begining of old age - Pereira Lopes, Maria Dos Anjos (Investigación y Educación en Enfermería, 2008)
When I was struck by a painful experience I took advantage of this event of life to reflect and I achieved deeper selfunderstanding, better knowledge of the aging process and of the sick persons body nursing care. This experience was framed as a preliminary in my Ph.D field-work and accordingly the use of self experience in qualitative research. Is a essential element to be considered. In this autobiographical account I discuss in the topics of my reflection: my body spoke while I did not understand it; the interruption of phisycal activities likened sickness; the radiographies envelope as a symbol; the set of small nursing cares that conserve us alive, the security feeling provided by the hospital; the fear of death and the alterations in the body’s image. Key words: Image, Old Age, Nursing cares, Self, Qualitative Research.